Large cell calcifying Sertoli cell tumour: a contemporary multi‐institutional case series highlighting the diagnostic utility of PRKAR1A immunohistochemistry. Issue 4 (5th January 2022) - Anderson, William J; Gordetsky, Jennifer B; Idrees, Muhammad T; Al‐Obaidy, Khaleel I; Kao, Chia‐Sui; Cornejo, Kristine M; Wobker, Sara E; Cheville, John C; Vargas, Sara O; Fletcher, Christopher D M; Hirsch, Michelle S; Acosta, Andrés M
Abstract : Aims: Large cell calcifying Sertoli cell tumour (LCCSCT) is a rare testicular sex cord‐stromal tumour that primarily affects young patients and is associated with Carney complex. We sought to characterise the clinicopathological features of a series of LCCSCT and evaluate the diagnostic utility of PRKAR1A immunohistochemistry (IHC). Methods and results: The LCCSCT cohort ( n  = 15) had a median age of 16 years (range = 2–30 years). Four patients were known to have Carney complex. PRKAR1A IHC was performed in each case. For comparison, PRKAR1A IHC was also assessed in other sex cord‐stromal tumours, including Sertoli cell tumour, not otherwise specified (SCT, NOS; n  = 10), intratubular large cell hyalinising Sertoli cell tumour ( n  = 1) and Leydig cell tumour ( n  = 23). Loss of cytoplasmic PRKAR1A expression was observed in all but one LCCSCT (14 of 15; 93%). PRKAR1A expression was retained in all SCTs, NOS (10 of 10; 100%), the majority of Leydig cell tumours (22 of 23; 96%) and an intratubular large cell hyalinising Sertoli cell tumour (1 of 1; 100%). One Leydig cell tumour showed equivocal staining (multifocal weak expression). Conclusions: Overall, PRKAR1A loss is both sensitive (93%) and highly specific (97%) for the diagnosis of LCCSCT. PRKAR1A loss may aid its diagnosis, particularly in sporadic cases and those that are the first presentation of Carney complex. Abstract :